No pain no gain: a survey of use of healthcare and reasons not to seek healthcare by Norwegian climbers with chronic injuries - Gudmund Grønhaug; Atle Saeterbakken (BMJ Open Sport & Exercise Medicine, 2019)
Objectives To assess the use of healthcare, and reasons not to seek healthcare, by climbers with a chronic injury.Method Retrospective survey.Setting Web-based questionnaire.Participants 667 active climbers (385 with chronic injuries).Outcome measure Use of healthcare (including reasons not to seek healthcare if the patient was not attended by health professionals), performance level in sport climbing, onset of a climbing-related injury, site of injury, preferred style of climbing and gender differences.Result Of the 667 respondents, 385 had experienced a chronic injury in the past 6 months. Climbers with a chronic injury are reluctant to seek healthcare, and male climbers are less likely to seek healthcare than female climbers. The two most frequent reasons not to seek healthcare were: (1) an assumption that the injury was not serious enough (70%) and (2) a belief that a health professional could not help (60%). Only one in five of the climbers with a finger injury sought healthcare. The more experienced climbers were less likely to seek healthcare than recreational climbers.Conclusion Use of healthcare among climbers with a chronic injury is limited and injured climbers self-assess the injury before seeking medical aid. Experience is a strong predictor for not seeking healthcare after an injury. These findings open up the possibility that some of those who do not seek healthcare after self-assessing the injury are underestimating the seriousness of the injury due to lack of confidence in the health professionals’ abilities to help treating chronic climbing related injuries.